Gandhi and the Idea of Sustainability— Implications for Science Education - Saxena, Astha (SCHOOL SCIENCE, 2020)
The principles of Sustainable Development (as highlighted in the Brundtland Commission*, 1987) entail the conservation of resources for the current and future generations without disturbing the ecological balance. The present paper discusses the role and relevance of Gandhian education philosophy and his vision of a School (at Sevagram Ashram) for sustainable living. The paper further delineates the scope of Gandhian education philosophy and ideals in the present-day context of school education and integrates his philosophy within the prescribed school curriculum. A case of a Class VI science textbook has been taken as an example to review and analyse the curriculum in the light of Gandhian principles and ideas of sustainability for school education. The paper also provides suggestions for further integration of Gandhian values of sustainability and sustainable development within the school curriculum. Educational implications can be drawn for science education in general, as well as for in-service and pre-service science teachers, teacher educators, and science curriculum developers.